Planning Skills of Adolescents With ADHD. Issue 1 (January 2018) - Boyer, Bianca E.; Geurts, Hilde M.; Van der Oord, Saskia
Objective: This study assesses planning skills of adolescents with ADHD using a multi-method assessment and explores subtype differences between inattentive and combined subtypes.Method: One hundred fifteen adolescents with ADHD and 34 typically developing controls completed subtests of the Delis–Kaplan Executive Function System (D-KEFS), Behavioral Assessment of the Dysexecutive Syndrome (BADS), and Behavior Rating Inventory of Executive Function (BRIEF).Results: No group differences were found on the D-KEFS. The BADS Zoo Map test showed longer completion times in the inattentive than in the combined subtype and controls. The BRIEF showed more planning problems in adolescents with ADHD (both subtypes) than in controls, with the combined subtype showing most problems on overall executive functioning.Conclusion: Only a proportion of adolescents with ADHD shows planning deficits. To capture these planning problems in adolescents with ADHD, it seems important to use multiple measures of planning, both ratings and "less structured" neurocognitive measures of planning.